In situ observations of graphitic staples in crumpled graphene. (June 2018) - Lin, Alex Y.W.; Yu, Xiao-xiang; Dato, Albert; Krauss, Gordon; Marks, Laurence D.
Abstract: Graphene is an exceptionally effective lubricant additive that performs well when crumpled rather than as flat sheets. In the literature, it has been suggested that crumpled graphene is analogous to wadding paper, and that this morphology significantly improves self-dispersion in lubricants and anti-wear behavior. We report here in situ transmission electron microscopy of crumpled graphene sliding, demonstrating that it possesses intra-sheet links and graphitic nanocrystals that provide additional mechanical stability and enable the material to reversibly deform. Crumpled graphene is closer to crumpled paper with additional staples, with the intra-sheet links and graphitic nanocrystals as graphitic staples. Graphical abstract: Image 1